Revisiting Classics: Relevance of Jane Austen's Pride and Prejudice - Lahiri, Rajyashree Khushu; Chakravarty, Urjani (EAST WEST JOURNAL OF HUMANITIES, 2011)
Although many readers and critics of the present era might consider Jane Austen's fictional writings to be outdated and clichéd, her work nevertheless retains an undying appeal. During the last decade of the twentieth century the English-speaking world has experienced an Austen renaissance as it has been treated to a number of film and television adaptations of her work. The reasons for viewers and readers enjoying and identifying with Austen's fiction are numerous. This paper contends that the 'mutual cognitive environment' which Jane Austen so skilfully and dexterously creates in her masterpiece Pride and Prejudice, accounts for its present day relevance and appeal. This claim will be elucidated and established through an analysis of the novel within the framework of the concept of a 'mutual cognitive environment' as explicated by Sperber and Wilson in their discussion of Relevance Theory (2002:249). The contention is prompted by the assumption that a comprehensive account of how this 'mutual cognitive environment' is created by Austen and the process of its interpretation by readers should generate accounts of how this text gives rise to particular effects. Further, the paper maintains that for the present-day reader of Pride and Prejudice this environment is created due to the interaction of contextual assumptions which include knowledge of hierarchical social status, predicament of women in a male-dominated society, and human traits.